The Mediating Role of Learning Engagement Between Self-Efficacy and Academic Achievement Among Chinese College Students - Qin Luo; Lunchao Chen; Dongfang Yu; Ke Zhang (2023)
The link between academic self-efficacy and academic achievement and its potential mediation by learning engagement was investigated in college students in China.